2013
DOI: 10.1002/app.38989
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of PVC/TiO2 nanorods: Surface tension and mechanical properties before and after UV exposure

Abstract: In this study, nanocomposites of poly(vinyl chloride) (PVC), using the synthesized titanium dioxide (TiO 2 ) nanorods and commercial nanopowder of titanium dioxide (Degussa P25) were produced by melt blending. The presence of TiO 2 nanorods in PVC matrix led to an improvement in mechanical properties of PVC nanocomposites in comparison with unfilled PVC. The photocatalytic degradation behavior of PVC nanocomposites were investigated by measuring their structural change evaluations, surface tension, and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The codes and composition of prepared PVC/TiO 2 nanocomposite samples were described in Table . The preparation procedure of the nanocomposites essentially was the same as described in our previous work . The average thickness of the films was measured about 0.71 mm for artificial weathering with the surface area of 12 × 25 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The codes and composition of prepared PVC/TiO 2 nanocomposite samples were described in Table . The preparation procedure of the nanocomposites essentially was the same as described in our previous work . The average thickness of the films was measured about 0.71 mm for artificial weathering with the surface area of 12 × 25 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Cho and Choi studied the photocatalytic degradation of PVC‐TiO 2 film in ambient air. On the other hand, studies about the screen effect of TiO 2 on inhibiting the photodegradation of PVC have also been reported. Anton‐Prinet et al found that the radiation of wavelength of 390 nm is close to the absorption cut‐off of TiO 2 (rutile type), which is mainly responsible for the improved UV resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In another study , it is reported that TiO 2 (rutile type) could not only decrease the rate of oxygen uptake, but also decrease the amount of HCl evolved. Sokhandani et al found that addition of TiO 2 nanorods could reinforce PVC and improve its UV resistance simultaneously. Other studies related to the surface modification of TiO 2 , and using TiO 2 (rutile type) in the PVC‐based wood‐plastics composites are also reported .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(vinyl chloride) (PVC) is one of the most important and widely in use thermoplastics because of its valuable properties, such as low production cost, good process ability, easy modification, and excellent chemical and fire resistance . The ultimate user acceptance of PVC products for outdoor building applications will depend on their stability to resist deterioration of their mechanical and aesthetic properties over long periods of exposure that is needed to a careful compounding . Because, the energy content of ultraviolet (UV) region can rupture the most chemical bonds of polymer structure 5 ; therefore, these PVC products are degraded under sun's UV radiation which leads to severe discoloration and loss of mechanical properties of these products .…”
Section: Introductionmentioning
confidence: 99%